Editorial - Kennedy, Hanuman (Ushus Journal of Business Management, 2021)
Human capital is the single most important capability asset within knowledge value chain driven corporations. In the organizations’ pursuit to become knowledge driven, it is essential to address human capital challenges with prime focus on attracting, retaining and sustaining knowledge workers. Some of the major challenges are in the domain of talent acquisition, engagement and retention. Current trends show increasing rates of job hopping, attitudinal changes, job dissatisfaction, expectancy with regard to increased payments, greater autonomy in workplace and instantaneous career growth. Organizations face dilemma choosing between investing on training potential candidates or on acquiring talent. As talent moves rapidly to countries with better economies, the focus should be on geographical retention. Unequal distribution of knowledge and expertise is highly rampant. Traditional monetary driven “performance causal value chains” is no longer effective in motivating the knowledge worker. Thus, the true challenge for any knowledge driven organization functioning in a dynamic environment is human capital management. This issue focuses on the research output in the area of Human Capital Challenges in knowledge driven organisations.